Variabilidade de atributos físicos de um latossolo vermelho sob cultivo de cana-de-açúcar - Pellin, Douglas Martins Pereira; Montanari, Rafael [UNESP]; Lima, Elizeu De Souza [UNESP]; Lovera, Lenon Henrique [UNESP]; Corrêa, Adriany Rodrigues [UNESP] (My University, 2015)
The goal of this paper was to select among the attributes surveyed soil, one with better repre-sentation to explain the variability of the technological components of sugar cane. The study was conducted at ETH Eldorado Plant in Rio Brilhante, MS, in the agricultural year 2011/2012, in a Oxisol, which was installed a geostatistical grid for data collection of soil and plant, with 80 sampling points, a 80 ha area. From the stand-point of linear and spatial TCH has been explained as a function of volumetric moisture. The volumetric mois-ture collected at a depth of 0.00 to 0.20 m, which had values between 0,24 to 0,270 m3 m-3, resulted in sites with the highest productivity of sugar cane per hectare from 64 to 70 t ha-1. To aid future studies aimed at preci-sion agriculture, which will use the same attributes as those of the future works, the values of ranges of spatial dependence to be used should be between 81 and 487 meters.
Variability of physical properties of an oxisol under cultivation of sugar cane
Keywords: Management and soil conservation; Precision agriculture; Saccharum spp; Spatial variability